Bomantara: Reinterpreting Batik Fabric Relief Surya Majapahit - Rizki Lestari (PT FORMOSA CENDEKIA GLOBAL, 2022)
With the development of the times, all aspects are competing to create new, creative and innovative things, including batik motifs. Various kinds of batik motifs in the archipelago make batik a cultural heritage full of diversity. The main element that should not be left behind from batik is the motif because behind the motif is stored prayer, hope for the wearer, one of which is a batik cloth with the name Bomantara.